Assessment of conditioning-specific movement tasks and physical fitness measures in talent identified under 16-year-old rugby union players - Parsonage, J. R.; Williams, R. S.; Rainer, P.; McKeown, I.; Williams, M. D. (The Journal of Strength and Conditioning Research, 2014)
Preparedness to train was assessed using a battery of conditioning-specific movement tasks (CSMTs) on a group of talent identified rugby union players (n = 156; age = 15 ± 7 years; stature = 176 ± 7 cm; and mass = 74 ± 14 kg). In addition to explore the link between movement competency and performance, a series of standard fitness tests was conducted. Overall the group's CSMTs competency ratings were low, but task dependent. The proportion of competent players ranged from 14% for a single leg squat to 70% for a double to single leg landing. Players were subsequently grouped based on their CSMTs ratings using cluster analysis. This analysis classified players on features of the CSMT battery that distinguished between groups rather than an arbitrary score. Fitness test scores were then compared between the 3 groups identified. The "general low competency" group jumped 9.1 cm lower (p = 0.0218), sprinted slower across 10, 20 and 40 m (range, p = 0.0126-0.0018) and covered 389 m less (p = 0.0105) Yo-Yo intermittent recovery level 1 distance compared with the "squat competent group." In summary, at this important time before academy selection, most players could not competently perform the CSMTs that underpin rugby conditioning and may not be prepared for the transition into the "training to compete" stage of the suggested long-term athlete development model. For this sample of players, the athlete development process may therefore be unnecessarily inhibited. Moreover, our observations that competency in some CSMTs may explain better running and jumping performances in some players suggest that a focus on monitoring and addressing movement competencies during the training to train stage of player development should be considered.